Total ultraviolet blocking polyvinylidene fluoride film and preparation method thereof
By combining modified polyvinylidene fluoride and titanium dioxide grafted modified aramid fiber, the problem of insufficient stain resistance and mechanical properties of polyvinylidene fluoride films is solved, and high ultraviolet and infrared barrier rates and flame retardant are achieved. Performance, meet high-demand application needs.
Patent Information
- Application Number
- CN202411539547.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyvinylidene fluoride films have poor stain resistance, insufficient mechanical properties, and are prone to damage during use, making it difficult to meet the high-demand application needs.
Using modified polyvinylidene fluoride and titanium dioxide grafted modified aramid fibers, the hydrophilicity, flame retardant properties and mechanical properties of the film are improved through modification reactions and surface treatment, and the entire UV is prepared through specific process steps. Barrier polyvinylidene fluoride film.
It has achieved high ultraviolet and infrared barrier rates, good stain resistance and flame retardant properties, and has excellent mechanical properties after film formation and strong scratch resistance.
Smart Images

Figure BDA0005112450570000021 
Figure BDA0005112450570000022 
Figure BDA0005112450570000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyvinylidene fluoride film preparation, and in particular to a full-ultraviolet blocking polyvinylidene fluoride film and a preparation method thereof. Background Art
[0002] PVDF, the full name of which is polyvinylidene fluoride, is a highly non-reactive thermoplastic fluorine-containing polymer. It is composed of homopolymers of vinylidene fluoride or copolymers of vinylidene fluoride and a small amount of fluorine-containing vinyl monomers, and the fluorine content is about 60%. Polyvinylidene fluoride has excellent resistance to chemical corrosion, high temperature, oxidation, weather, UV and high temperature radiation. In addition, it also exhibits excellent tensile strength and impact strength, high hardness and wear resistance, high heat deformation temperature, and good creep fatigue resistance. It has a wide operating temperature range, from -60°C to 150°C. It is a strong and tough structural material that is widely used in coatings, biomedicine, water treatment and other fields.
[0003] However, due to the low friction coefficient of polyvinylidene fluoride itself, it is not easy to bond during processing, resulting in defects such as weak strength, short life, and reduced mechanical properties of the membrane material made of polyvinylidene fluoride. For example, CN115000622B discloses "PVDF coated diaphragm and preparation method thereof". PVDF slurry is prepared with polymethyl methacrylate, sodium dodecylbenzene sulfate, polymethyl methacrylate, chitosan, styrene-butadiene latex, PVDF powder, palm oil, and acetone, and ceramic slurry is prepared with polyacrylamide, sodium alginate, ceramic powder, water, and ethanol. Fluoroalkyl ethoxy alcohol ether, ceramic slurry and PVDF slurry are mixed, coated and dried to obtain a PVDF coated diaphragm with strong mechanical properties.
[0004] For example, CN108047836B discloses “a super-weather-resistant PVDF double-layer powder coating and its preparation method”. The two phases of different components are treated separately, and then mixed and crushed in a reaction kettle. The PVDF double-layer powder coating has good adhesion and high impact resistance.
[0005] In addition, since polyvinylidene fluoride itself is highly hydrophobic, the membrane material made of it has poor stain resistance during use and is difficult to clean. For example, CN108246124B discloses "a method for preparing a PVDF membrane with catalytic self-cleaning function" by grafting 4-aminopyridine on PVDF and then coordinating metal phthalocyanine, and then blending it with PVDF. The PVDF membrane has good hydrophilicity, improved anti-fouling performance and imparted self-cleaning ability, but the problem it solves is relatively single and its scope of application is limited.
[0006] Therefore, it is urgent to develop a polyvinylidene fluoride film with good stain resistance, excellent mechanical properties after film formation and scratch resistance. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a full UV blocking polyvinylidene fluoride film and a preparation method thereof. The polyvinylidene fluoride film of the present invention has high UV and infrared blocking rates, good flame retardancy and stain resistance, excellent mechanical properties after film formation and scratch resistance.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] On the one hand, the present invention provides a full UV blocking polyvinylidene fluoride film, comprising the following raw materials in parts by weight: 80 to 90 parts of modified polyvinylidene fluoride, 20 to 24 parts of titanium dioxide grafted modified aramid fiber, 10 to 14 parts of polymethyl methacrylate, 1 to 5 parts of inorganic filler, 30 to 40 parts of deionized water and 30 to 40 parts of anhydrous ethanol.
[0010] In some embodiments, the method for preparing the modified polyvinylidene fluoride comprises the following steps:
[0011] A1. Mix fumaric acid, 1,3-dihydroxyacetone and solvent, add dilute sulfuric acid, heat to 60-70°C and stir for 12-16 hours. After the reaction, cool to 0-5°C, add saturated sodium bicarbonate solution until no bubbles are generated, concentrate under reduced pressure, extract with ethyl acetate, concentrate the organic phase under reduced pressure and dry, and obtain the compound shown in Formula I.
[0012]
[0013] A2. Mix the compound represented by formula I in step A1, 2-aminoethylphosphonic acid, piperidine, trimethyl orthoformate and solvent, raise the temperature to 60-70°C and stir at constant temperature for 6-8h. After the reaction is completed, concentrate and dry under reduced pressure, and perform column chromatography to obtain the compound represented by formula II
[0014]
[0015] A3. Mix the compound represented by formula II in step A2, vinylidene fluoride, sodium dodecyl sulfate and water, add potassium persulfate and sodium sulfite and stir for 10 to 15 minutes, raise the temperature to 60 to 70°C and stir at a constant temperature for 6.5 to 7.5 hours. After the reaction is completed, centrifuge and filter, wash with anhydrous ethanol to obtain modified polyvinylidene fluoride.
[0016] Due to its strong hydrophobicity, polyvinylidene fluoride has poor antifouling property and is not easy to clean in some application environments, especially when used as an air membrane material on outdoor buildings. The present application first makes a functional monomer, and then copolymerizes it with polyvinylidene fluoride to obtain modified polyvinylidene fluoride, which also contains a large number of hydroxyl and phosphoric acid groups, greatly increasing the hydrophilicity of the modified polyvinylidene fluoride, thereby improving the antifouling property of the film. In addition, the applicant has found that the modified polyvinylidene fluoride improves the plasticity and flame retardant properties of the film. The reason may be that the modified polyvinylidene fluoride contains a large number of ester groups in its structure. Due to the presence of ester groups, the modified polyvinylidene fluoride interacts with the polar groups of other substances in the film raw material system, thereby reducing the intermolecular force and increasing the flexibility of the film. At the same time, because its structure contains a large number of phosphoric acid groups, the flame retardant properties of the film are improved.
[0017] In some embodiments, the solvent is anhydrous methanol and / or anhydrous ethanol.
[0018] Preferably, the solvent is anhydrous ethanol.
[0019] In some embodiments, in step A1, the volume of the solvent is 6 to 8 times the total mass of fumaric acid and 1,3-dihydroxyacetone.
[0020] Preferably, in step A1, the volume of the solvent is 7 times the total mass of fumaric acid and 1,3-dihydroxyacetone.
[0021] In some embodiments, in step A1, the mass concentration of the dilute sulfuric acid is 45-50%.
[0022] Preferably, in step A1, the mass concentration of the dilute sulfuric acid is 47%.
[0023] In some embodiments, in step A1, the mass ratio of the dilute sulfuric acid to 1,3-dihydroxyacetone is (0.4-0.6):1.
[0024] Preferably, in step A1, the mass ratio of the dilute sulfuric acid to 1,3-dihydroxyacetone is 0.5:1.
[0025] In some embodiments, in step A1, the molar ratio of fumaric acid to 1,3-dihydroxyacetone is 1:(2-2.2).
[0026] Preferably, in step A1, the molar ratio of fumaric acid to 1,3-dihydroxyacetone is 1:2.1.
[0027] The applicant adjusted the molar ratio of fumaric acid to 1,3-dihydroxyacetone so that the two active carboxyl groups in the fumaric acid could undergo esterification reaction and be replaced, so that the compound structure shown in Formula I does not contain a carboxyl group, thereby preventing the carboxyl group from reacting with the amine group in 2-aminoethylphosphonic acid in step A2, thereby reducing the hydrophilicity of the modified polyvinylidene fluoride. In addition, it can also prevent the problem of excessive crosslinking density during copolymerization of the compound shown in Formula II with vinylidene fluoride due to excessive double bond content in the compound shown in Formula I, resulting in reduced film toughness.
[0028] In some embodiments, in step A2, the molar ratio of the compound represented by formula I, 2-aminoethylphosphonic acid, piperidine and trimethyl orthoformate is 1:(2-2.2):(1-1.2):(1-1.2).
[0029] Preferably, the molar ratio of the compound represented by formula I, 2-aminoethylphosphonic acid, piperidine and trimethyl orthoformate is 1:2.1:1.1:1.1.
[0030] In some embodiments, in step A2, the volume of the solvent is 7 to 9 times the mass of the compound represented by formula I.
[0031] Preferably, in step A2, the volume of the solvent is 8 times the mass of the compound represented by formula I.
[0032] In some embodiments, in step A3, the molar ratio of the compound represented by formula II to vinylidene fluoride is (0.04-0.06):1.
[0033] Preferably, in step A3, the molar ratio of the compound represented by formula II to vinylidene fluoride is 0.05:1.
[0034] The applicant can prevent the mechanical properties of the modified polyvinylidene fluoride from decreasing by adjusting the molar ratio of the compound represented by formula II and vinylidene fluoride.
[0035] In some embodiments, the method for preparing the titanium dioxide grafted modified aramid fiber comprises the following steps:
[0036] B1, soaking the aramid fiber in an ethanol solution for ultrasonic treatment, and then washing and drying with deionized water to obtain pretreated aramid fiber;
[0037] B2, passing the pretreated aramid fiber in step B1 through a low-temperature plasma generator, controlling the argon gas flow rate to 8-9 mL / min, and treating for 4-6 min at a plasma discharge power of 75-85 W to obtain a surface-treated aramid fiber;
[0038] B3, mixing butyl titanate, glacial acetic acid and anhydrous ethanol, stirring at room temperature for 30 to 40 minutes to obtain a mixed solution A;
[0039] B4, mixing anhydrous ethanol and deionized water and adjusting the pH to 3-4 with dilute hydrochloric acid to obtain a mixed solution B;
[0040] B5, at room temperature, adding the mixed solution B in step B4 dropwise to the mixed solution A in step B3, and stirring at room temperature for 2 to 3 hours to obtain a titanium dioxide gel;
[0041] B6. Soak the surface treated aramid fiber in step B2 in the mixture of titanium dioxide gel and propylene oxide in step B5, place it in an oven at 100-140° C. for heat treatment for 30-40 min, remove the surface treated aramid fiber in step B2, and dry it to obtain titanium dioxide grafted modified aramid fiber.
[0042] The applicant found in the research process that the addition of aramid fiber can improve the high temperature resistance and insulation performance of the film, but the conventional aramid fiber has low surface activity and poor dispersion with the system, which leads to the decline of film performance. The present application first performs plasma surface treatment on the aramid fiber to load a large number of active groups on its surface, and then mixes it with titanium dioxide gel and propylene oxide to improve its dispersion performance in the system. In addition, the applicant unexpectedly found that the titanium dioxide grafted modified aramid fiber can also improve the mechanical properties and stain resistance of the film. The reason may be that propylene oxide can make the aramid fiber have a cross-linked three-dimensional network structure, which improves the tensile resistance of the film. At the same time, the titanium dioxide gel can be loaded on the surface of the aramid fiber, thereby improving the self-cleaning performance of the film and thus improving the stain resistance. In addition, the introduction of titanium dioxide can maximize the ultraviolet barrier performance of the film, and is also conducive to improving the infrared reflection performance of the film.
[0043] In some embodiments, in step B3, the volume ratio of butyl titanate, glacial acetic acid and anhydrous ethanol is 1:(0.7-0.9):(0.15-0.25).
[0044] Preferably, in step B3, the volume ratio of butyl titanate, glacial acetic acid and anhydrous ethanol is 1:0.8:0.2.
[0045] In some embodiments, in step B4, the volume ratio of anhydrous ethanol to deionized water is 1:(0.4-0.6).
[0046] Preferably, in step B4, the volume ratio of anhydrous ethanol to deionized water is 1:0.5.
[0047] In some embodiments, in step B6, the mass ratio of the titanium dioxide gel to propylene oxide is 1:(0.05-0.07).
[0048] Preferably, in step B6, the mass ratio of the titanium dioxide gel to propylene oxide is 1:0.06.
[0049] The applicant can prevent the aramid fiber cross-linking structure from being too dense, which would lead to a decrease in the toughness of the film, by adjusting the mass ratio of titanium dioxide gel and propylene oxide.
[0050] In some embodiments, the inorganic filler is a mixture of alumina ceramic powder and nano-silicon dioxide, and the mass ratio of the two is 1:(0.2-0.5).
[0051] On the other hand, the present application provides a method for preparing a fully UV-blocking polyvinylidene fluoride film, comprising the following steps: mixing modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler, deionized water and anhydrous ethanol and stirring them thoroughly for 30 to 40 minutes to obtain a mixed slurry, then coating the mixed slurry on the surface of a substrate and drying it at 65 to 75°C for 20 to 30 minutes to obtain a fully UV-blocking polyvinylidene fluoride film.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The present invention adopts modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler and deionized water as main raw materials to prepare a full UV blocking polyvinylidene fluoride film, which has high UV and infrared blocking rates, good flame retardancy and stain resistance, excellent mechanical properties after film formation and is scratch resistant.
[0054] (2) The modified polyvinylidene fluoride of the present invention has good anti-fouling performance, and the modified polyvinylidene fluoride contains a large number of ester groups in its structure, which reduces the intermolecular force and increases the plasticity of the film. At the same time, since its structure contains a large number of phosphate groups, the flame retardant performance of the film is improved.
[0055] (3) The titanium dioxide grafted modified aramid fiber of the present invention has good dispersibility in the system. At the same time, propylene oxide can make the aramid fiber have a cross-linked three-dimensional network structure, thereby improving the tensile strength of the film. In addition, the titanium dioxide gel can be loaded on the surface of the aramid fiber, thereby improving the self-cleaning performance of the film and thus improving the stain resistance. The introduction of titanium dioxide can also maximize the ultraviolet barrier performance of the film, and is also beneficial to improving the infrared reflection performance of the film. DETAILED DESCRIPTION
[0056] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] In the following preparation examples, embodiments and comparative examples, aramid fiber was purchased from Jiangxi Shuobang New Material Technology Co., Ltd.; polymethyl methacrylate was purchased from Dongguan Zhengtao Plastic Co., Ltd.; alumina ceramic powder was purchased from Hebei Yuechao Wear-Resistant Materials Co., Ltd.; polyvinylidene fluoride was purchased from Dongguan Baojia Plastic Co., Ltd.
[0058] Preparation Example 1
[0059] The preparation method of modified polyvinylidene fluoride comprises the following steps:
[0060] A1. Mix 1 mol of fumaric acid, 2.1 mol of 1,3-dihydroxyacetone and 2.1 L of anhydrous ethanol, add 50 g of 47% dilute sulfuric acid, heat to 65°C and stir for 14 h. After the reaction, cool to 3°C, add saturated sodium bicarbonate solution until no bubbles are generated, concentrate under reduced pressure, extract with ethyl acetate, concentrate the organic phase under reduced pressure and dry to obtain the compound shown in Formula I.
[0061]
[0062] A2, 1 mol of the compound represented by formula I in step A1, 2.1 mol of 2-aminoethylphosphonic acid, 1.1 mol of piperidine, 1.1 mol of trimethyl orthoformate, and 2 L of anhydrous ethanol were mixed, the temperature was raised to 65°C and stirred at constant temperature for 7 hours, after the reaction was completed, the mixture was concentrated and dried under reduced pressure, and the compound represented by formula II was obtained by column chromatography.
[0063]
[0064] A3. Mix 0.05 mol of the compound represented by formula II in step A2, 1 mol of vinylidene fluoride, 0.02 mol of sodium dodecyl sulfate and 600 mL of deionized water, add 0.06 g of potassium persulfate and 0.06 g of sodium sulfite, stir for 13 min, heat to 65 ° C and stir at constant temperature for 7 h. After the reaction is completed, centrifuge and filter, wash with anhydrous ethanol to obtain modified polyvinylidene fluoride.
[0065] Preparation Example 2
[0066] The preparation method of modified polyvinylidene fluoride is the same as that of Preparation Example 1, except that the amount of fumaric acid added is 4 mol.
[0067] Preparation Example 3
[0068] The preparation method of modified polyvinylidene fluoride is the same as that of Preparation Example 1, except that the amount of vinylidene fluoride added is 0.4 mol.
[0069] Preparation Example 4
[0070] The preparation method of titanium dioxide grafted modified aramid fiber comprises the following steps:
[0071] B1, soaking 20g of aramid fiber in 100mL of 95% volume concentration ethanol solution for ultrasonic treatment, and then washing and drying with deionized water to obtain pretreated aramid fiber;
[0072] B2, passing the pretreated aramid fiber in step B1 through a low-temperature plasma generator, controlling the argon gas flow rate to 8 mL / min, and treating for 5 min at a plasma discharge power of 80 W to obtain a surface-treated aramid fiber;
[0073] B3, 100 mL of butyl titanate, 80 mL of glacial acetic acid, and 20 mL of anhydrous ethanol were mixed, and stirred at room temperature for 35 min to obtain a mixed solution A;
[0074] B4, 90 mL of anhydrous ethanol and 45 mL of deionized water were mixed and the pH was adjusted to 3 with 10 wt % dilute hydrochloric acid to obtain a mixed solution B;
[0075] B5, at room temperature, the mixed solution B in step B4 was added dropwise to the mixed solution A in step B3 at a rate of 5 mL / min, and stirred at room temperature for 2.5 h to obtain a titanium dioxide gel;
[0076] B6. Soak the surface treated aramid fiber in step B2 in a mixture of 300 g of the titanium dioxide gel in step B5 and 18 g of propylene oxide, place it in an oven at 120° C. for heat treatment for 35 min, take out the surface treated aramid fiber in step B2, and dry it to obtain the titanium dioxide grafted modified aramid fiber.
[0077] Preparation Example 5
[0078] The preparation method of titanium dioxide grafted modified aramid fiber has the same specific implementation method as Preparation Example 4, except that the mass of propylene oxide is 26 g.
[0079] Preparation Example 6
[0080] The preparation method of titanium dioxide grafted modified aramid fiber has the same specific implementation method as Preparation Example 4, except that the mass of propylene oxide is 12 g.
[0081] Example 1
[0082] A full-ultraviolet blocking polyvinylidene fluoride film comprises the following raw materials in parts by weight: 85 parts of modified polyvinylidene fluoride, 22 parts of titanium dioxide grafted modified aramid fiber, 12 parts of polymethyl methacrylate, 3 parts of inorganic filler, 35 parts of deionized water and 35 parts of anhydrous ethanol.
[0083] Among them, the modified polyvinylidene fluoride is prepared by Preparation Example 1; the titanium dioxide grafted modified aramid fiber is prepared by Preparation Example 4; and the inorganic filler is a mixture of 2.3 parts of alumina ceramic powder and 0.7 parts of nano-silicon dioxide.
[0084] The preparation method of the full UV blocking polyvinylidene fluoride film of the present embodiment includes the following steps: mixing modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler, deionized water and anhydrous ethanol and stirring them for 35 minutes to obtain a mixed slurry, then coating the mixed slurry on the surface of the substrate with a coating thickness of 80 μm, and drying at 70°C for 25 minutes to obtain a full UV blocking polyvinylidene fluoride film.
[0085] Example 2
[0086] A full-ultraviolet blocking polyvinylidene fluoride film comprises the following raw materials in parts by weight: 80 parts of modified polyvinylidene fluoride, 20 parts of titanium dioxide grafted modified aramid fiber, 10 parts of polymethyl methacrylate, 1 part of inorganic filler, 30 parts of deionized water and 30 parts of anhydrous ethanol.
[0087] Among them, the modified polyvinylidene fluoride is prepared by Preparation Example 1; the titanium dioxide grafted modified aramid fiber is prepared by Preparation Example 4; and the inorganic filler is a mixture of 0.8 parts of alumina ceramic powder and 0.2 parts of nano-silicon dioxide.
[0088] The preparation method of the full UV blocking polyvinylidene fluoride film of the present embodiment includes the following steps: mixing modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler, deionized water and anhydrous ethanol and stirring them for 30 minutes to obtain a mixed slurry, then coating the mixed slurry on the surface of the substrate with a coating thickness of 80 μm, and drying at 65°C for 30 minutes to obtain a full UV blocking polyvinylidene fluoride film.
[0089] Example 3
[0090] A full-ultraviolet blocking polyvinylidene fluoride film comprises the following raw materials in parts by weight: 90 parts of modified polyvinylidene fluoride, 24 parts of titanium dioxide grafted modified aramid fiber, 14 parts of polymethyl methacrylate, 5 parts of inorganic filler, 40 parts of deionized water and 40 parts of anhydrous ethanol.
[0091] Among them, the modified polyvinylidene fluoride is prepared by Preparation Example 1; the titanium dioxide grafted modified aramid fiber is prepared by Preparation Example 4; and the inorganic filler is a mixture of 3.3 parts of alumina ceramic powder and 1.7 parts of nano-silicon dioxide.
[0092] The preparation method of the full UV blocking polyvinylidene fluoride film of the present embodiment comprises the following steps: mixing modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler, deionized water and anhydrous ethanol and stirring them for 40 minutes to obtain a mixed slurry, then coating the mixed slurry on the surface of the substrate to a coating thickness of 80 μm, and drying at 75°C for 25 minutes to obtain a full UV blocking polyvinylidene fluoride film.
[0093] Example 4
[0094] A full UV blocking polyvinylidene fluoride film and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polyvinylidene fluoride is prepared by Preparation Example 2.
[0095] Example 5
[0096] A full UV blocking polyvinylidene fluoride film and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the modified polyvinylidene fluoride is prepared by Preparation Example 3.
[0097] Example 6
[0098] A full UV blocking polyvinylidene fluoride film and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the titanium dioxide grafted modified aramid fiber is prepared by Preparation Example 5.
[0099] Example 7
[0100] A full UV blocking polyvinylidene fluoride film and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the titanium dioxide grafted modified aramid fiber is prepared by Preparation Example 6.
[0101] Comparative Example 1
[0102] A full UV blocking polyvinylidene fluoride film and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal mass portion of polyvinylidene fluoride is used instead of modified polyvinylidene fluoride.
[0103] Comparative Example 2
[0104] A full UV blocking polyvinylidene fluoride film and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal mass portion of aramid fiber is used instead of titanium dioxide grafted modified aramid fiber.
[0105] Performance Test:
[0106] (1) Tensile strength test: Tested according to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets";
[0107] (2) Elongation at break test: Tested according to ASTM D882 "Standard Test Method for Tensile Properties of Plastic Sheets";
[0108] (3) Elongation test: Tested according to ASTM-D882-09 "Standard Test Method for Tensile Properties of Plastics";
[0109] (4) Infrared blocking rate and ultraviolet blocking rate: tested using Shimadzu UV-3600i Plus ultraviolet-visible-near-infrared spectrophotometer;
[0110] (5) Flame retardant performance test: Tested according to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0111] The polyvinylidene fluoride films of the embodiments and comparative examples were tested according to the above test method. The results are shown in Table 1.
[0112] Table 1
[0113]
[0114] According to the data in Table 1, the polyvinylidene fluoride films of Examples 1 to 3 have good mechanical properties, flexibility, infrared and ultraviolet blocking rates, and good flame retardancy; in Example 4, due to the change in the molar ratio of fumaric acid to 1,3-dihydroxyacetone, the tensile strength and elongation at break of the film material increased, but the flexibility of the film decreased; in Example 5, due to the change in the molar ratio of the compound shown in Formula II to vinylidene fluoride, the mechanical properties of the film decreased, and the ultraviolet blocking rate decreased; in Example 6, due to the change in the molar ratio of titanium dioxide gel and propylene oxide, the mechanical properties of the film decreased, and the ultraviolet blocking rate decreased. The mass ratio of titanium dioxide gel to propylene oxide was changed, and the increase of propylene oxide content resulted in the increase of mechanical properties of the film, but the flexibility was greatly reduced; Example 7 also changed the mass ratio of titanium dioxide gel to propylene oxide, and the decrease of propylene oxide content resulted in the decrease of mechanical properties of the film; Comparative Example 1 used equal mass parts of polyvinylidene fluoride instead of modified polyvinylidene fluoride, resulting in the decrease of elongation and flame retardant properties of the film; Comparative Example 2 used equal mass parts of aramid fiber instead of titanium dioxide grafted modified aramid fiber, resulting in the decrease of anti-ultraviolet, infrared and mechanical properties of the film.
[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A full UV blocking polyvinylidene fluoride film, characterized in that: The invention comprises the following raw materials in parts by weight: 80 to 90 parts of modified polyvinylidene fluoride, 20 to 24 parts of titanium dioxide grafted modified aramid fiber, 10 to 14 parts of polymethyl methacrylate, 1 to 5 parts of inorganic filler, 30 to 40 parts of deionized water and 30 to 40 parts of anhydrous ethanol.
2. The full UV blocking polyvinylidene fluoride film according to claim 1, characterized in that: The preparation method of the modified polyvinylidene fluoride comprises the following steps: A1. Mix fumaric acid, 1,3-dihydroxyacetone and solvent, add dilute sulfuric acid, heat to 60-70°C and stir for 12-16 hours. After the reaction, cool to 0-5°C, add saturated sodium bicarbonate solution until no bubbles are generated, concentrate under reduced pressure, extract with ethyl acetate, concentrate the organic phase under reduced pressure and dry, and obtain the compound shown in Formula I. A2. Mix the compound represented by formula I in step A1, 2-aminoethylphosphonic acid, piperidine, trimethyl orthoformate and solvent, raise the temperature to 60-70°C and stir at constant temperature for 6-8h. After the reaction is completed, concentrate and dry under reduced pressure, and perform column chromatography to obtain the compound represented by formula II A3. Mix the compound represented by formula II in step A2, vinylidene fluoride, sodium dodecyl sulfate and water, add potassium persulfate and sodium sulfite and stir for 10 to 15 minutes, raise the temperature to 60 to 70°C and stir at a constant temperature for 6.5 to 7.5 hours. After the reaction is completed, centrifuge and filter, wash with anhydrous ethanol to obtain modified polyvinylidene fluoride.
3. The full UV blocking polyvinylidene fluoride film according to claim 2, characterized in that: The solvent is anhydrous methanol and / or anhydrous ethanol.
4. The full UV blocking polyvinylidene fluoride film according to claim 2, characterized in that: In step A1, the molar ratio of fumaric acid to 1,3-dihydroxyacetone is 1:(2-2.2).
5. The full UV blocking polyvinylidene fluoride film according to claim 2, characterized in that: In step A2, the molar ratio of the compound represented by formula I, 2-aminoethylphosphonic acid, piperidine and trimethyl orthoformate is 1:(2-2.2):(1-1.2):(1-1.2).
6. The full UV blocking polyvinylidene fluoride film according to claim 2, characterized in that: In step A3, the molar ratio of the compound represented by formula II to vinylidene fluoride is (0.04-0.06):
1.
7. The full UV blocking polyvinylidene fluoride film according to claim 1, characterized in that: The method for preparing the titanium dioxide grafted modified aramid fiber comprises the following steps: B1, soaking the aramid fiber in an ethanol solution for ultrasonic treatment, and then washing and drying with deionized water to obtain pretreated aramid fiber; B2, passing the pretreated aramid fiber in step B1 through a low-temperature plasma generator, controlling the argon gas flow rate to 8-9 mL / min, and treating for 4-6 min at a plasma discharge power of 75-85 W to obtain a surface-treated aramid fiber; B3, mixing butyl titanate, glacial acetic acid and anhydrous ethanol, stirring at room temperature for 30 to 40 minutes to obtain a mixed solution A; B4, mixing anhydrous ethanol and deionized water and adjusting the pH to 3-4 with dilute hydrochloric acid to obtain a mixed solution B; B5, at room temperature, adding the mixed solution B in step B4 dropwise to the mixed solution A in step B3, and stirring at room temperature for 2 to 3 hours to obtain a titanium dioxide gel; B6. Soak the surface treated aramid fiber in step B2 in the mixture of titanium dioxide gel and propylene oxide in step B5, place it in an oven at 100-140° C. for heat treatment for 30-40 min, remove the surface treated aramid fiber in step B2, and dry it to obtain titanium dioxide grafted modified aramid fiber.
8. The full UV blocking polyvinylidene fluoride film according to claim 7, characterized in that: In step B6, the mass ratio of the titanium dioxide gel to propylene oxide is 1:(0.05-0.07).
9. The full UV blocking polyvinylidene fluoride film according to claim 1, characterized in that: The inorganic filler is a mixture of alumina ceramic powder and nano silicon dioxide, and the mass ratio of the two is 1:(0.2-0.5).
10. A method for preparing the full UV blocking polyvinylidene fluoride film according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing modified polyvinylidene fluoride, titanium dioxide grafted modified aramid fiber, polymethyl methacrylate, inorganic filler, deionized water and anhydrous ethanol and stirring them fully for 30 to 40 minutes to obtain a mixed slurry; then coating the mixed slurry on the surface of a substrate and drying it at 65 to 75°C for 20 to 30 minutes to obtain a fully UV-blocking polyvinylidene fluoride film.
Citation Information
Patent Citations
A super weather-resistant PVDF double-layer powder coating and its preparation method
CN108047836B
A method for preparing a PVDF membrane with catalytic self-cleaning function
CN108246124B
PVDF coated diaphragm and preparation method thereof
CN115000622B
Method for preparing polyvinylidene fluoride film
CN104231496A
High-waterproofing scratch-resistant polyvinylidene fluoride film and preparation method therefor
CN107501815A